The Continuous Classical Optimal Control of a Couple Nonlinear Hyperbolic Partial Differential Equations with Equality and Inequality Constraints - Al-Hawasy, Jamil A. Ali (Iraqi Journal of Science, 2022)
This paper is concerned with the existence of a unique state vector solution of a couple nonlinear hyperbolic equations using the Galerkin method when the continuous classical control vector is given, the existence theorem of a continuous classical optimal control vector with equality and inequality vector state constraints is proved, the existence of a unique solution of the adjoint equations associated with the state equations is studied. The Frcéhet derivative of the Hamiltonian is obtained. Finally the theorems of the necessary conditions and the sufficient conditions of optimality of the constrained problem are proved.